REVIEW: A crusade for media truth and justice - David Robie (Asia Pacific Network, 2018)
The First Casualty: From the Front Lines of the Global War on Journalism, by Peter Greste. Sydney: Viking. 2017. 335 pages. ISBN 9780670079261.